Cryptococcal meningitis and cerebral venous thrombosis in a sickle cell anemia patient - Isabel González Alemán; Claudia Roche Albernas; Betty Alonso Falcón; Grethel Dueñas Ramírez; Maylín Acosta Álvarez; Leonel Valdés Leiva; José Luis Rodríguez Monteagudo; Yilena Rodríguez Marrero; Agneris López Saserio; Rosa Oliday Ríos Jiménez; Eric González Fernández; Alexis Morales Valdera; et al. (Acta Médica del Centro, 2012)
A 47-year-old woman diagnosed with sickle cell anemia and a vaso-occlusive crisis in the brain was admitted with fever, general malaise and headache, with transient episodes of disorientation. In her evolution, there was a motor defect in the right side, dysarthria and convulsive seizures refractory to therapy. The cranial tomographic study revealed a hypodense image in the left parietal lobe in relation with an infarction, and evidence of contrast enhancement in the turns in the affected area due to cortical vein thrombosis. The patient had a torpid evolution, and died with neurological impairment and septic respiratory symptoms. At necropsy, it was concluded the presence of Cryptococcus neoformans meningitis and cerebral venous thrombosis in a sickle cell anemia patient, associated with severe bilateral bacterial bronchopneumonia that lead to her death. Infections in immunocompromised patients, and especially fungal infections, may not be suspected and may not be treated, as occurred with this patient. This fact, and the association with cerebral venous thrombosis, motivated a discussion in the clinicopathological session of the institution. The study of the autopsy is reported, as well as a review of the condition as a way of focusing attention on opportunistic fungal infections. This is another tough battleground for the diagnosis and treatment of patients, in which the main weapon is the proper use of the epidemiological-clinical method in all medical specialties – efforts must be directed that way.